(untitled) - Matthews, Martin S. (New York, 2010)
To create a dynamic page on which content changes in response to events requires programming and the potential use of databases. Dynamic Web Programming: A Beginner's Guide starts by covering HTML, XHTML, and CSS. You will then learn to use JavaScript to implement elements such as rollover events, popups, and calculations. The book explains how to use PHP to create guest books, blogs, and page transitions, as well as how to implement a database-driven Web site with MySQL.
Keywords: Web sites,Web; Design,Thiết kế